From outreach to outcome: exploring the impact of integrated marketing communication on the performance of small and medium-sized enterprises - Vinod Sharma; Yogesh Mahajan; Manohar Kapse (Cogent Business & Management, 2024)
There is a growing need for small and medium-sized businesses (SMEs) to employ Integrated Marketing Communication (IMC) components to develop a robust brand-focused communications strategy given the present uncertain market circumstances and the consequent market volatility. For SMEs, the IMC pillars are crucial for building a robust strategic presence, which in turn improves company success. A descriptive cross-sectional study was employed to establish the link between IMC components and business performance. Data from 845 SME managers or owners were collected from India and were analyzed using PLS-SEM. The results show a strong correlation between the five dimensions of IMC performance and enhanced company performance. The results of the moderation analysis also show that Market Orientation has little effect on the connection between IMC features and Business Performance. In this article, we'll look at how SMEs can improve their company performance plans by incorporating market orientation and integrated marketing communication (IMC). SMEs, especially those in the service industry, would benefit greatly from this study's findings regarding the need to use this managerial approach to boost SME performance.
Keywords: 650; Market orientation; service industry; small and medium- sized enterprises (sMes); business performance; integrated marketing communication